ปัจจัยที่สัมพันธ์ต่อการกำเริบของโรคในผู้ป่วยโรคไตอักเสบลูปัส - ขันทอง เขียวงาม (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The leading causes of mortality in SLE patients are infection and relapse resulting from a complication of Lupus nephritis. Therefore, prevention of recurrence of the Lupus nephritis by slowing the degeneration and promoting the renal function is a significant treatment for the SLE patients. To be accomplished, factors related to inducing the relapse need to be controlled. This study aimed to determine factors associated with disease relapses in Lupus Nephritis patients. A case-control study in Lupus nephritis outpatients at King Chulalongkorn Memorial hospital and Nopprarat Rajathanee hospital was conducted during November 1, 2013 to January 31, 2014. There were 169 patients (74 patients in a study group and 95 patients in a control group). Data were collected by interviewing the respondents. Univariate analysis was used to examine the factors associated with disease relapses and logistic regression was used to estimate odds ratios and 95% confidence intervals. The results showed that the factors associated with disease relapse in Lupus nephritis were blood pressure (adjusted OR = 3.12, 95% CI 1.00-9.71) infection (adjusted OR = 3.12, 95% CI 1.38-7.03) organ involvements (adjusted OR = 3.10, 95% CI 1.46-6.53) noncompliance (adjusted OR = 3.26, 95% CI 1.42-7.52) and stress (adjusted OR = 4.11, 95% CI 1.75-9.68). Consequently, paying attention to such factors is essential to prevent relapse, enhance the quality of life of Lupus nephritis patients.